Development of Problem-Based Learning (PBL) E-worksheet on Comparative Material - Oktavera, Cherryn; Izzati, Nur (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2023)
This research was conducted to the lack of availability of teaching materials based on the student's need, namely variations in the use of teaching materials that are suitable for use in the learning process. This research aims to determine the feasibility of the developed e-worksheet. It used Research and Development (R&D) with a 4D development model. The subjects were 26 students of class VII.6 of Tanjungpinang 6 Junior High School (SMP). The data collection instrument was a validation questionnaire assessed by material expert validators, linguists and media experts. The results of the validation obtained regarding the eligibility information of the e-worksheet, with the assessment of material experts, obtained a percentage of 81% in the valid category, the assessment of language experts obtained a percentage of 76% in the very valid category, and the assessment of the media obtained a percentage of 73% in the valid category. Based on the overall data analysis results, it was concluded that the developed PBL-based e-worksheet was declared feasible and could be used in learning mathematics.